Fact-Finding Study on the Association between Mothers Aware of Dysphoric Milk Ejection Reflex and Psychiatric Disorders - Kitaoka, Nao; Tateoka, Yumiko (Journal of Midwifery, 2024)
Dysphoric milk ejection reflex (D-MER) is a transient discomfort that occurs during milk secretion. A study was conducted to identify the association between psychiatric disorders and D-MER symptoms and support mothers with D-MER who have a history of psychiatric disorders. Questionnaires on basic information, awareness of D-MER, and coping with D-MER were distributed online to people who were at least 18 years old during the survey and had no history of postpartum depression. The responses of those who had experienced D-MER were analyzed. Among participants with a history of D-MERS, 58.2% (64 participants) and 85.5% (94 participants) had a history of depression and psychiatric disorders, respectively. Those with a history of depression had significantly longer symptoms than those without a history of depression (P=0.005), and were more likely to have difficulty losing confidence due to D-MER symptoms (P=0.011). The results suggest that a history of psychiatric disorders is associated with the onset of D-MER. It was inferred that reduced serotonin secretion may lead to a greater reduction in dopamine, which is required for the secretion of prolactin for milk production.